UPAYA PENINGKATAN KREATIVITAS ANAK DI SD NEGERI KARANGPUCUNG 1 DENGAN PELATIHAN SENI DAN BUDAYA - M Ilham Rahmani Riyadi; Febri Isnawati; Khanza Zalsabila (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
Early childhood has a high curiosity, so attention is needed that is not only pursuing achievement, but learning orientation that develops attitudes and interest in learning and stimulates various potentials and basic abilities of children. Therefore the design of painting activities will be the right choice to be used for creativity during this covid pandemic. This PKM painting activity was carried out at the Cimone Orphan House in Tangerang with presentation of the material and then continued with painting practice. The target of this service program is the elementary and junior high school level as many as 15 (fifteen) people. The implementation was carried out face-to-face (on the spot training) which began with observation and coordination with the management of the orphanage related to the availability of places, the readiness of the orphans and administrative licensing arrangements with the administrators of the orphanage. The method used in carrying out PKM activities is to increase children's creativity, showing examples of pots that you want to decorate / pictures using Microsoft PowerPoint in the form of pictures, playing games with orphans, and asking questions / quizzes. The results of the service to students increase knowledge, insight and creativity of orphans.